Answer :

Using log a – log b = log

Put y = vx

Differentiate vx with respect to x using product rule

Integrate

Substitute log v = t

Differentiate with respect to v which means

⇒ log t = log x + log c

Resubstitute value of t

⇒ log(log v) = log x + log c

Resubstitute v

Hence solution of given differential equation is

Rate this question :

Solve the differential equation :

(tan^{-1}y – x)dy = (1 + y^{2})dx.

**OR**

Find the particular solution of the differential equation given that y = 1, when x = 0.

Mathematics - Board PapersSolve the following differential equation:

Mathematics - Board Papers

Find the particular solution of the differential equation given that when

Mathematics - Board PapersShow that the differential equation (x e^{y/x} + y)dx = xdy is homogeneous. Find the particular solution of this differential equation, given that x = 1 when y = 1.

Solve the differential equation:

given that when

Mathematics - Board PapersFind the particular solution of the following differential equation. given that when x = 2, y = π

Mathematics - Board Papers